2015
DOI: 10.1093/hmg/ddv367
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sodium/proton exchanger NHE3 activity causes congenital sodium diarrhea

Abstract: Congenital sodium diarrhea (CSD) refers to an intractable diarrhea of intrauterine onset with high fecal sodium loss. CSD is clinically and genetically heterogeneous. Syndromic CSD is caused by SPINT2 mutations. While we recently described four cases of the non-syndromic form of CSD that were caused by dominant activating mutations in intestinal receptor guanylate cyclase C (GC-C), the genetic cause for the majority of CSD is still unknown. Therefore, we aimed to determine the genetic cause for non-GC-C non-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 38 publications
3
96
0
4
Order By: Relevance
“…Mutations in the DRA gene lead to congenital chloride diarrhea (24) and defective Cl Ϫ /HCO Ϫ exchange functions on the BBM of villus enterocytes (37). Impaired Na ϩ absorption due to the reduced functional activity of NHE3 is the underlying cause of congenital sodium diarrhea (28). Reduction in the surface area of the small intestine due to the villus atrophy and loss of MVs can further account for the absorptive loss (45) in MVID.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the DRA gene lead to congenital chloride diarrhea (24) and defective Cl Ϫ /HCO Ϫ exchange functions on the BBM of villus enterocytes (37). Impaired Na ϩ absorption due to the reduced functional activity of NHE3 is the underlying cause of congenital sodium diarrhea (28). Reduction in the surface area of the small intestine due to the villus atrophy and loss of MVs can further account for the absorptive loss (45) in MVID.…”
Section: Discussionmentioning
confidence: 99%
“…Classical or non-syndromic CSD results from loss-of-function mutations in the Na/H + exchanger NHE3, which is critical for normal Na + and fluid absorption from the intestine, as well as normal acid-base homeostasis. 37 CSD also results from activating mutations in the guanylin receptor GC-C (GUCY2C), resulting in elevated cellular cyclic guanosine monophosphate levels, inhibition of NHE3 function, and stimulation of chloride secretion via CFTR chloride channels. 50 Lastly, a syndromic form of CSD (SPINT2) that overlaps in phenotype with CTE has been decribed.…”
Section: Disorders Of Epithelial Nutrient/electrolyte Transportmentioning
confidence: 99%
“…(10,11,25) While it has been shown that diarrhea associated with ulcerative colitis (UC) occurs primarily as the result of inhibition of NHE-mediated Na + absorption in UC, (30) …”
Section: Ibd As a Consequence Of Loss Of Nhe3 Functionmentioning
confidence: 99%